EKSPLORASI ETNOMATEMATIKA PADA BENTUK JAJANAN PASAR DI DAERAH JEPARA UNTUK PEMBELAJARAN MATEMATIKA SMP - Dian Naila Apriyanti; Putri Nur Malasari (Universitas Bhinneka PGRI, 2024)
In the cultural context, traditional market snacks in the Jepara area have the potential to integrate ethnomathematics into mathematics learning. Traditional market snacks in Jepara offer various forms of snacks in which there is a geometric concept. The purpose of this study is to find out the concept of geometry in traditional market snacks in the Jepara area. In this study, qualitative methods are used with an ethnographic approach. The objects studied by the researcher were 5 traditional market snacks, with 3 respondent subjects, namely traditional market snack sellers found in Jepara market, Pecangaan market, and Tegalsambi market. Several techniques for collecting data are used in this study, including observation techniques, interviews, and documentation. Based on the research conducted by the researcher, the results were obtained that there are geometric concepts and cultural elements in 5 traditional market snacks in the Jepara area, including a ball-shaped klepon, a rectangular layer, a ball-shaped onde-onde, a triangular prism-shaped banana bongko, and a solid half-ball shaped kintelan. The results of this research are expected to function as an effective alternative learning resource to introduce geometry concepts to students.